Spinal cord trauma : neural repair and functional recovery - McKerracher, L. (Lisa); Doucet, G. (Guy); Rossignol, Serge, 1942-; Reeve, Christopher, 1952-2004 (Progress in brain research, 2002)
This book covers, in a broad perspective, research on spinal cord injury, beginning with human spinal cord injury to experimental studies in animals, to molecular mechanisms of injury and regeneration. Every year 12,000 will suffer spinal cord injury leading to permanent disability. In the last five years enormous progress has been made in the understanding of spinal cord injury, and in ways to elicit repair in animal models of spinal cord injury. The scope includes animal models of spinal cord injury, strategies for neuroprotection and regeneration, and possible roles of axon guidance molecules in injury and regeneration. Topical reviews are presented as well as new data on timely issues in spinal cord injury research.